PROBLEMS OF USING FLEXIBLE THERMOPLASTIC HOSES IN COLD CLIMATE - Y. N. Ribakov; O. D. Harlamova; S. I. Chirikov (Научный вестник МГТУ ГА, 2016)
The possibility of using pressure thermoplastic hoses in the Arctic and the Far North is evaluated. The conclusion that the replacement of rubber hoses on the thermoplastic will reduce 2.5 times their material consumption, extend the 10-15 C temperature range of operating temperatures, eliminate the influence of sleeve material on fuel quality, improve the strength characteristics and terms of use is presented.